Recent Experiences and Advances in Contrast-Enhanced Subharmonic Ultrasound. (18th May 2015) - Eisenbrey, John R.; Sridharan, Anush; Liu, Ji-Bin; Forsberg, Flemming
Abstract : Nonlinear contrast-enhanced ultrasound imaging schemes strive to suppress tissue signals in order to better visualize nonlinear signals from blood-pooling ultrasound contrast agents. Because tissue does not generate a subharmonic response (i.e., signal at half the transmit frequency), subharmonic imaging has been proposed as a method for isolating ultrasound microbubble signals while suppressing surrounding tissue signals. In this paper, we summarize recent advances in the use of subharmonic imaging in vivo . These advances include the implementation of subharmonic imaging on linear and curvilinear arrays, intravascular probes, and three-dimensional probes for breast, renal, liver, plaque, and tumor imaging.